Strategi Peningkatan Penerimaan Pajak Bumi dan Bangunan (PBB) : Studi Kasus di Kabupaten Klaten - Pratiwi DK (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2002)
In order to get regional development fund in local government, it was done many ways to increase local income both from local revenue or out local revenue, one of income source that potentially increased is Land and Building Tax (hereafter called PBB). So that, there should be certain strategies that could increase the income of PBB in localgovernment This paper deals strategic management approach to indentii, strategic factors, strategic issues and strategies that could be developed to increase the income of PBB. Thispaperis result of case study research in local government of Klaten. The result of strategic environment analysis (SWOT)for Revenue Office in local government of Klaten , it was identified 28 factor that influence the income of PBB, including 7 Strength , 6 Weaknesses, 9 Opportunities, and 6 Threats. From the analysis of both internal and external factors and after the litmus test and the evaluation of PEST aspect, it could be identfied4 most strategic issues in increasing the income of PBB in localgovernment of Klaten , there are the increasing valuation of object of PBB( hereafter talledNJOP), increasing the PBB intensification, PBB computerized and Data rejuvenation . The recommended strategies for increasing the income of PBB in local government of .Klaten are :for responding the NJOP increasing issue, it recommended the strategy of evaluating, review, adjust the old ITT, and determine a new NJOP of NJOP of PBB, the strategy for responding data rejuvenation issue is optimized the registry, data collection and valuation of subject and object of PBB,. for responding the issue of increasing PBB intensification, the recommended strategy is optimizing PBB intensification, increase people and government awareness and closes the service and the recommeded strategyforreVodingPBB computerized issue is increasing and perfection a gstim of PBB computerized.